Pengaruh Store Atmosphere, Persepsi Harga, dan Kelengkapan Produk terhadap Keputusan Pembelian pada Swalayan Pamenang Pagu Kediri - Erica Sophiyanti; Anita Sumelvia Dewi; Angga Permana Mahaputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
This study aims to explain and prove the hypothesis about whether there is an influence of store atmosphere, price perceptions, and product completeness on purchasing decisions at Pamenang Pagu Kediri Supermarkets. This research uses descriptive research with quantitative methods with sampling techniques, namely Nonprobability Sampling with the accidental method with a total population of 300 respondents and a sample of 75 respondents who are consumers at Pamenang supermarkets. The analysis technique used is validity test, reliability test, classic assumption test, multiple linear regression test, t test (partial) F test (simultaneous), and the determinant coefficient (R2) which is processed using the SPSS version 25 program. The conclusions of this study that partially store atmosphere has no significant effect on purchasing decisions obtained a significant value of 0.206> 0.05. Perceived price partially has a significant effect on purchasing decisions with a significant value of 0.000 <0.05. Product completeness partially has a significant effect on purchasing decisions with a significant t value obtained for 0021 <0.05. Store atmosphere, price perception, and product completeness simultaneously have a significant effect on purchasing decisions with an F test value of 0.000 <0.05.